Research on Control Strategy of Improved Single-phase Active Power Filter - Gang Hu; Chuan Zang; Ya-jie Ma; Zhi-guo Xiao; Wei-li Dai (Institute of Advanced Engineering and Science, 2014)
Unipolar single-phase active power filter control strategies need to the transformers and adders. Moreover, the circuits to fulfill the control strategy are more complicated. In order to solve above problems, an improved unipolar modulation control strategy has been performed in this paper. The principle of control strategy was analyzed in detail in this paper and related simulation has been finished. The results of simulation show that this improved control strategy can simplify the structure of circuit without affecting the system performance index. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4817